Monkeypox: A New Epidemic Threat with Behavioral Components of Physical Intimacy? Diante do contexto de uma possível epidemia e possibilidade de pandemia ocasionada pela varíola dos macacos, e esta pode ser uma patologia relacionada à transmissão sexual - Sampaio de Souza Morais, Julia; Salles, Roberto de Souza; Coêlho, Ivo Castelo Branco (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Given the context of a possible epidemic and the possibility of a pandemic caused by monkeypox, this may be a pathology related to sexual transmission. It is relevant to question and demand from national and international health authorities which measures to adopt to contain the disease and not repeat the mistakes of previous situations.